Thermal performance and energy savings of a ground-sink heat pump for air conditioning system - Rosniah Che Abdullah (Penerbit Universiti Malaysia Perlis, 2011)
This study reports a thermal performance and energy savings between a ground-sink heat pump (GSHP) system and an air-sink heat pump (ASHP) system. The systems connected to a test room in the School of Environmental Engineering, University Malaysia Perlis, were designed and constructed for space cooling. The performances of GSHP and the ASHP system were experimentally determined. The experimental results were obtained from 22 to 28 March 2011 in hot humid climate for which the data taken every 15 minutes in 12 hours a day. The average coefficient of performance (COP) was determined using the measured absolute temperature of the cooled space and heat sinks. COP of the GSHP system of the horizontal exchanger was obtained to be 2.77 and COP of the ASHP system was determined to be 2.43. The average power consumption of GSHP system was calculated to be 3.6 kilowatt while the power consumption of the ASHP system was obtained to be 4.3 kilowatt per 12 hours the systems running. The test results indicate that system parameters and the climate condition could have an important effect on performance and that GSHP systems are economically preferable to ASHP systems if any improvement may be made for GSHP upgrading systems in further studies.